Semi-supervised Infrared Small Target Detection with Thermodynamic-Inspired Uneven Perturbation and Confidence Adaptation - Zhang, Mingjin; Shang, Wenteng; Gao, Fei; Zhang, Qiming; Lu, FengQin; Zhang, Jing (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Single-frame Infrared Small Target (SIRST) detection has made significant advancements, but it still faces challenges due to limited labeled data and the foreground-background class imbalance. To address these issues, we introduce a novel Semi-Supervised SIRST Detection (S^3D) pipeline in this paper. First, drawing inspiration from thermodynamics, we propose augmenting infrared images using both chromatically and spatially uneven perturbations. This dual-stream perturbation enhances the diversity and balance of infrared samples, contributing to the robustness of detection models. Additionally, we develop a confidence-adaptive matching method to maintain weighted consistency among perturbed unlabeled samples. Second, to tackle class imbalance in labeled data, we compel the model to generate discriminative predictions for challenging, misclassified examples while down-weighting well-classified examples. We achieve this by modifying the standard cross-entropy loss to squeeze the detector and truncating the loss on well-classified examples. Our innovative Truncated Squeeze (TS) loss focuses on learning discriminative representations for difficult cases and prevents over-optimization for simpler ones. To assess the effectiveness of the perturbation techniques and loss functions, we apply them to various SIRST detectors and conduct comprehensive experiments on two benchmark datasets. Notably, our proposed methods consistently and significantly improve accuracy. Remarkably, our approach achieves over 98% performance of the state-of-the-art fully-supervised method using only 1/8 of the labeled samples.